PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS MULTIMEDIA INTERAKTIF PADA MATERI TURUNAN FUNGSI - Priliyanti, Priliyanti (Universitas Ahmad Dahlan, 2012)
This study aims to design and develop interactive multimedia-based learning media on the topic derivatives function and knowing students interest while using the interactive multimedia-based learning media on the topic derivatives function. This research is a development of a model ADDIE (Analysis, Design, Development, Implementation, and Evaluation) used to produce a product. The product is mathematics learning media interactive multimedia-based. The research is carried out at SMA 2 Yogyakarta. The research data is obtained from the questionnaire validation media by media experts, questionnaire validation media by media matter experts, questionnaire evaluation media by student questionnaires and student interest questionnaire. The research data are analyzed quantitatively and qualitatively for the purpose of media evaluation. The analysis phase determines that the material is packaged in a learning media. The learning media is the derivative function which is developed using Macromedia Flash 8. At the development stage, media and materials experts conduct a trial of small groups that aim to test the media feasibility. Media validation questionnaire obtains percentage of 85,44% and 77,60%, and both of percentage are good category. In the implementation stage, a field test is conducted to test the learning media and knowing students interest towards the learning media. Students media evaluation questionnaire obtains percentage of 74,38% and 74,06% of interest questionnaire. It is concluded that the mathematics learning media interactive multimedia-based in the topic derivatives and function is feasible and can attract students learning interest in using learning media. Key words : learning media, ADDIE, derivative function